Tantangan Perlindungan Dana Nasabah pada Layanan Equity Crowdfunding di Era Industri 4.0: Analisis Peraturan OJK - Wandra Wardiansha Purnama (Universitas Medan Area, 2023)
This study analyzes customer fund protection within equity crowdfunding services in the Industry 4.0 era, with a focus on OJK regulations. The aim is to comprehend the responsibilities of organizers and their impact on public trust. The research employs a normative juridical method with a legislative approach and conceptual analysis of OJK regulations and relevant literature. The findings underline the need for stronger regulations to safeguard customer funds and maintain transparency within the services. Consequently, it is crucial for organizers adhere regulations to sustain public trust. In conclusion, enhancing customer fund protection in equity crowdfunding requires active collaboration among stakeholders and the updating of pertinent regulations.